2018
DOI: 10.1111/jhn.12565
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Canada's Food Guide recommendations among Alberta's multi‐ethnic youths is a major concern: findings from the WHY ACT NOW project

Abstract: The majority of youths did not consume minimum daily recommended servings of Vegetables and Fruit, Milk and Alternatives, and/or Meat and Alternatives food groups. Evidence-based dietary interventions and public health strategies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…In a study conducted in a Canadian university community (653 staff members, 2490 students), more than 49% of staff members and about 46% of students did not meet the recommendations for Milk & Alternatives [ 29 ]. Kolahdooz et al conducted a study in a sample of Alberta’s multi-ethnic youths aged 11–23 years and found that the percentage of youths not meeting recommendations for Milk & Alternatives was 81.7% for Indigenous, 73.3% for African & Middle Eastern, 78.6% for Asian and 63.5% for European youths [ 30 ]. Results from a longitudinal study conducted in a sample of Canadian grade 9–12 students (ages 13–18 years) showed that only a quarter of students (24.9%) met the recommendations for Milk & Alternatives at both time points [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in a Canadian university community (653 staff members, 2490 students), more than 49% of staff members and about 46% of students did not meet the recommendations for Milk & Alternatives [ 29 ]. Kolahdooz et al conducted a study in a sample of Alberta’s multi-ethnic youths aged 11–23 years and found that the percentage of youths not meeting recommendations for Milk & Alternatives was 81.7% for Indigenous, 73.3% for African & Middle Eastern, 78.6% for Asian and 63.5% for European youths [ 30 ]. Results from a longitudinal study conducted in a sample of Canadian grade 9–12 students (ages 13–18 years) showed that only a quarter of students (24.9%) met the recommendations for Milk & Alternatives at both time points [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies reviewed were based on the evaluation of breakfast [13,[23][24][25][26][27][28][29][30], on the analysis of adolescents' daily consumption or on overall eating habits [31][32][33][34][35][36][37][38] and on the relationship of diet with physical activity [39][40][41][42] or with school performance [15,[43][44][45]. We also found some educational interventions [42,[46][47][48][49][50][51][52] and studies that focused on adherence to the Mediterranean diet [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…The results also suggest that caloric intake may be an area to address with individuals who identify more severe levels of anxious and depressive symptoms, given the negative health implications associated with it. The findings underscore the need to involve primary care (e.g., student health centers) in screening for psychological symptoms of distress given the association between increased risk of developing chronic diseases and poor nutrition [83]. This need is echoed in the recommendations made by the U.S. Preventative Services Task Force (USPSTF) to include screening for depression in all primary care practices [84].…”
Section: Clinical Impactmentioning
confidence: 93%